Transition from CZTSe to CZTS via multicomponent CZTSSe: Potential low cost photovoltaic absorbers. (January 2018) - Chawla, Parul; Jain, Shefali; Vashishtha, Parth; Ahamed, Mansoor; Sharma, Shailesh Narain
Abstract: A quintessential perspective for elaborating the pivotal role of quinary chalogenides such as CZTSSe plunges the thrust for exploration of non-vacuum approach for development of multicomponent chalcogenides utilizing organic surfactants and solvents for the nanocrystals ideal for photovoltaic applications.The piece of study envisages employment of TOPO-TOP as capping agents-cum-solvents for the very first time and have not been reported for CZTSSe-based materials till date. The work has been forwarded with the variation of anionic ratios in pristine counterparts of CZTSSe; i.e. CZTSe and CZTS in order to envision the potential of quinary chalcogenides wherein properties of two different materials coalesce to impart improved characteristics in CZTSSe. Varying Se:S ratios gradually during nanocrystals' synthesis by high-temperature colloidal route ensued precise control over the phase formation and morphology. With the employment of these capping agents, as-synthesized nanocrystals' are inherently Se-rich and high crystallinity restrains the need for selenization and high temperature annnealing respectively. Graphical abstract: Transitional studies from CZTSe to CZTS via a potential photovoltaic absorber CZTSSe using organic capping ligand such as TOPO-TOP has been implemented subsequently. The study demonstrates the variation of anionic ratios and their role in improving structural, morphological and optical properties in the quaternary system.Image Highlights: Colloidal synthesis of quaternary CZTSe, CZTS and potential CZTSSe have been executed. Synthesis of multicomponent CZTSSe using organic TOPO-TOP reported for the first time. From CZTSe to CZTS via varying anionic ratios, explores the potential of CZTSSe. Formation of highly-crystalline nanocrystals of CZTSSe & other related materials ensued. Compositional probing reflects the restrainment of high temperature selenization.